2008
DOI: 10.1039/b713646c
|View full text |Cite
|
Sign up to set email alerts
|

Aromaticity and antiaromaticity in transition-metal systems

Abstract: Aromaticity is an important concept in chemistry primarily for organic compounds, but it has been extended to compounds containing transition-metal atoms. Recent findings of aromaticity and antiaromaticity in all-metal clusters have stimulated further research in describing the chemical bonding, structures and stability in transition-metal clusters and compounds on the basis of aromaticity and antiaromaticity, which are reviewed here. The presence of d-orbitals endows much more diverse chemistry, structure and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
256
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 263 publications
(278 citation statements)
references
References 64 publications
(91 reference statements)
9
256
0
2
Order By: Relevance
“…Among them, four bonding orbitals with a 1g and t 1u symmetry are fully occupied, giving a ground-state electronic configuration of (a 1g ) 2 (t 1u ) 6 , whereas four antibonding orbitals with t 2g and a 2u symmetry are completely empty. The bonding pattern of the eight MOs is comparable to those of Au 3 þ and benzene molecules that have the famous planar s-and p-aromaticity 34 and obey Hückel's 4n þ 2 rule (Supplementary Fig. 15).…”
Section: Synthesesmentioning
confidence: 78%
“…Among them, four bonding orbitals with a 1g and t 1u symmetry are fully occupied, giving a ground-state electronic configuration of (a 1g ) 2 (t 1u ) 6 , whereas four antibonding orbitals with t 2g and a 2u symmetry are completely empty. The bonding pattern of the eight MOs is comparable to those of Au 3 þ and benzene molecules that have the famous planar s-and p-aromaticity 34 and obey Hückel's 4n þ 2 rule (Supplementary Fig. 15).…”
Section: Synthesesmentioning
confidence: 78%
“…Recently discovered [11], all-metal and semimetal aromatic clusters represent one of the new boundaries of material science (three recent reviews on this kind of clusters can be found in Refs. [12][13][14]). The unusual stability of all these clusters comes from their aromatic character.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the aromaticity is a key property of these compounds since it explains their molecular and electronic structure, stability, and reactivity. At variance with the classical aromatic organic molecules that possess only π-electron delocalization, these compounds present σ-, π-, and δ-(involving d orbitals) [15][16][17] or even φ-(involving f orbitals) [18] electron delocalization, exhibiting characteristics of what has been called multifold aromaticity [12][13][14][19][20][21][22]]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further progress in this area involves theoretical and experimental studies of all-metal clusters with several chemical compositions. [4][5][6][7][8][9][10][11][12][13] The most commonly used theoretical method to deal with metal clusters is the single-particle density functional theory (DFT). It is well known that, due to approximate exchangecorrelation (XC) energy, DFT usually cannot predict results within the chemical accuracy.…”
Section: Introductionmentioning
confidence: 99%